Analysis of the Needs of Elementary School Students in Learning Lontara Script - Mirfan, Mirfan; Yaumi, Muhammad; Akib, Erwin (PPSDP International Journal of Education, 2024)
Learning the Lontara script in elementary schools still faces various obstacles, especially in terms of less interactive teaching methods and limitations of interesting learning media. Conventional methods such as lectures and writing exercises in books are often less effective in improving student understanding. This study aims to analyze the learning needs of the Lontara script with a Visual, Auditory, and Kinesthetic (VAK) approach to better suit the learning characteristics of students. The research method used is qualitative descriptive, with data collection techniques through observation, interviews, and questionnaires to students and teachers in elementary schools. The results showed that 40% of students have visual learning styles, 35% auditory, and 25% kinesthetic, so learning media that accommodates these three learning styles is needed. The visual approach can be applied through infographics and animation, auditory through songs or voice narratives, and kinesthetics through writing exercises based on digital technology. The conclusion of this study confirms that the integration of the VAK approach in learning the Lontara script can increase the effectiveness and interest in learning of students. Therefore, it is recommended to develop technology-based learning media, such as augmented reality (AR) and digital applications, to create learning that is more innovative, interactive, and in accordance with the times.